Precision Nitrogen Management for Rice in Mid-Hills of Nepal: Productivity, Profitability and Nitrogen Use Efficiency - Poudel, Sunita; Amgain, Lal Prasad; Gaire, Achyut; Kaduwal, Sangita (Journal of Agriculture and Forestry University, 2026)
Nepalese farmers often apply generalized nitrogen (N) recommendations that overlook fieldspecific conditions, leading to excessive N use, higher costs, and reduced efficiency. This study evaluated the effectiveness of precision N management tools on rice yield, economic returns, and nitrogen use efficiency in the mid-hills of Nepal. A field trial was conducted during the 2024 monsoon season in the mid-hills of Nepal using a Randomized Complete Block Design with seven treatments and three replications. The treatment included Control (N0 – 0 kg N ha-1), Farmers’ Fertilizer Practice (FFP- 138 kg N ha-1), National Recommendation (NR- 100 kg N ha-1), Leaf Color Chart (LCC- 61.33 kg N ha-1), Soil Plant Analysis Development (SPAD- 33.33 kg N ha-1) meter, Normalized Difference Vegetation Index (NDVI) based Green Seeker (58.33 kg N ha-1), and Nutrient Expert (NE- 113.5 kg N ha-1) model. Grain yield, economic performance, partial factor productivity of Nitrogen (PFPN), and Agronomic Nitrogen use efficiency (ANUE) were measured and analyzed using Analysis of Variance and DMRT at a 5% significance level. All the nitrogen-fertilized treatments significantly outperformed the control. The NE treatment produced the highest grain yield (6.79 Mt ha-1), statistically at par with NR (6.65 Mt ha-1). The NE treatment provided the highest gross returns (NRs 260,481.4 ha-1), net return (NRs 115,531.27 ha-1), and benefit-cost ratio (1.63). However, the SPAD meter-based treatment, which applied the least amount of nitrogen (33.33 kg ha-1), achieved the highest PFPN (137.57 kg grain kg-1 N) and ANUE (49.50 kg yield increase kg-1 N), significantly surpassing all other treatments, including the FFP, which recorded the lowest efficiency. The findings demonstrated that real-time, site-specific precision nitrogen management tools, particularly NE and sensor-based approaches like SPAD meter, enhance productivity, profitability, and nitrogen use efficiency. Further multi-season and multi-location studies are recommended to validate and refine these precision management tools for wider adoption across diverse agro-ecological regions of Nepal.